The effectiveness of agricultural certification in developing countries: A systematic review. (December 2018) - Oya, Carlos; Schaefer, Florian; Skalidou, Dafni
Highlights: We find positive effects on prices and income from sale of certified products. However, we find no change in overall household income and assets. Wages for workers are not higher in certified production. Context is crucial in explaining variation in effects. Impact evaluations on certification need better study design and reporting. Abstract: Certification systems (CS) set and monitor voluntary standards to make agricultural production sustainable in socio-economic terms and agricultural trade fairer for producers and workers. They try to achieve a wide range of socio-economic and environmental effects through bundles of interventions that include the process of standard setting and compliance, advocacy among consumers, capacity building for producers, building supply chains, price interventions, and the application of acceptable labour standards, overall to improve the wellbeing of farmers and agricultural workers. This paper presents the results of a mixed-method systematic review that synthesized the literature on socio-economic effects of certification systems on agricultural producers and wage workers in low and middle income countries. The review followed the Campbell Collaboration guidelines for systematic reviews, and included studies published between 1990 and 2016 in different languages, with evidence on low and middle income countries. The review included a quantitative effectiveness question focused on a range of intermediate (e.g. prices, wages) and endpoint outcomes (e.g. household income). It also included a question on barriers, facilitators and contextual factors shaping effectiveness which drew on qualitative or mixed-method studies. Eligible certification systems were based on second- (industry-level) or third-party certifications, and excluded own-company standards. For the effectiveness review, quantitative impact evaluations must use experimental or non-experimental methods demonstrating control for selection bias. With these inclusion criteria, the review includes 43 studies used for analysing quantitative effects, and 136 qualitative studies for synthesizing barriers, enablers and other contextual factors. Most included studies report on initiatives in Latin America and sub-Saharan Africa and focus primarily on agricultural producers. The quality of the included studies is mixed, and several studies are weak on a number of methodological fronts, especially on statistical reporting. Overall, there is limited and mixed evidence on the effects of CS on a range of intermediate and final socio-economic outcomes for agricultural producers and wage workers. There are positive effects on prices and income from the sale of produce is higher for certified farmers. However, workers' wages do not seem to benefit from the presence of CS and, further along the causal chain, we find no evidence that total household income improves with certification. The integrated synthesis of quantitative and qualitative studies shows that context matters substantially in all causal chains and multiple factors shape the effectiveness and causal mechanisms that link interventions associated with certification and the wellbeing of producers, workers and their families.